Ethical Issues in the Contemporary World: The Case of Boko Haram in Nigeria - Cornelius A , Omeike (African Journal of Education,Science and Technology (AJEST), 2016)
Contemporary ethical issues predominantly proliferate in particular continents and among certain religions. They are issues arising from gay- marriage, abortion, euthanasia, capital punishment, extermination of or amnesty to adherents of Boko Haram and the Niger Delta militant. The case of Boko Haram in Nigeria argues for a re-definition of “ethics” according to some selfish opinions and even more, from erudite powerful influential voices. A proper response to an ethical issue should comply with what people consider moral, acceptable and convenient despite all arguments. The solution of the contemporary ethical issues cannot lie on which school of thought is politically right, which continent is more developed, or whose ideas could be tagged primitive. Without falling into the mean arising out of two evils which is logically unacceptable, one ought to determine the historical origins of Boko Haram, the proponents and its vision. A grasp of attendant issues will enable one discern whose convenience the Sect serves and to whose detriment. The case of Boko Haram’s emergence will in this way be seen as attracting no ethical sympathy. Innovation, as Plato’s view on Education holds, should lead people out of the cave (Stumpf, S.E., 1971) and not endanger human species. Ethical solutions should be just, impartial and objective.